Effectiveness of Multimodal Communicative Practices in Higher Artistic Education: An Analysis of Contemporary Approaches - Tkach, Marlia; Kozyr, Alla; Mymryk, Mykhailo; Holubytska, Nadiia; Khomych, Iryna (Journal of educational technology development and exchange, 2025)
The relevance of the study is driven by the fact that in today’s world, higher education is increasingly oriented towards interactivity and the utilization of various resources. The aim of this article is to explore various aspects of multimodality and formulate key communicative practices in higher artistic education. Addressing the stated problem is based on theoretical methodology, including methods such as surveys, analytical approaches including historical and hermeneutic analysis, comparative methods, and systematization. Research findings demonstrate that multimodality effectively enriches the learning process, fosters critical thinking, and deepens understanding of subjects. Digital technologies contribute to enhancing students’ technological literacy, preparing them for the challenges of an information society. Utilizing visual and auditory aspects makes learning more engaging and enhances student interest and motivation. Among the main communicative practices widely applied in modern higher artistic education institutions are (a) integration of various media formats, (b) adaptation to different learning styles, (c) optimal balance between real and virtual components, (d) flexibility in online and offiine learning, (e) structured use of technologies, and (g) interactivity and interaction. Further research could focus on studying methods for developing students’ cultural competence in artistic environments. The findings of this research may be beneficial for educators, pedagogy scholars, and students in higher artistic education institutions.